Korelasi Bahasa Daerah, Kesenian, dan Pariwisata (Kajian Integratif Terhadap Bahasa Aceh) - Teguh Santoso (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2014)
This paper contain about the integration beetwen art, language, and tourism. Aceh is one of province inIndonesia that have many wealth of them.This article tries to reveal the wealth of art, language and thesupporting the Aceh tourism. The arts use the Aceh language such as tari seulaweuet, tari rapai, tari phoetc. If that arts using the Aceh language, it is very important to revitalitation. Revitalitation can use anyway or method. Some of the method is by using the internet media, and supporting the goverment, includingthe private sector. by the integration beetwen art and language, the tourism sector can be increased asshown by the statistic person who come to Aceh as a tourist. This paper contain about the integration beetwen art, language, and tourism. Aceh is one of province in Indonesia that have many wealth ofthem.This article tries to reveal the wealth of art, language, and the supporting the Aceh tourism. The artsuse the Aceh language such as tari seulaweuet, tari rapai, tari pho etc. If that arts using the Acehlanguage, it is very important to revitalitation. Revitalitation can use any way or method. Some of themethod is by using the internet media, and supporting the goverment, including the private sector. By theintegration beetwen art and language, the tourism sector can be increased as shown by the statisticperson who come to Aceh as a tourist.